Synthesis and Characterization of some new Matals Complexes of (POPIONYL CARBAMOTHIOYL) Valine (PCV) - Saad S. Jaber, Basima M. Sarhan (Pakistan Journal of Medical & Health Sciences, 2022)
A new ligand was prepared (PCV) (popionylcarbamothioyl)valine by reacting (popionyl chloride)with ammonium thiocyanate in a ratio of (1:1)mole and adding it to 1mol of valine . The precise analysis of the elements(C,H,N,S) and FTIR spectra and (UV-Vis)measurements of ligand(PCV). The metal ion complexes are created and characterized using (FTIR) and (UV-vis) spectroscopy, magnetic susceptibility, atomic absorption, and conductivity studies. From The formula for calculating the findings is as follows: "[M(PCV)2] where M+2 is Mn, Co,Ni,Cu,Zn,Cd,Hg". since the complexes are thought to have a tetrahedral structure excluding the copper , which has a square planer geometry.